Studies of plasma parameters in low pressure discharge initiated in coaxial waveguide by microwave stochastic radiation - Karas, V.I.; Alisov, A.F.; Yegorov, A.M.; Karas, I.V.; Karelin, S.Yu.; Zagrebelny, I.A. (Вопросы атомной науки и техники, 2016)
It is shown, to create an effective discharge, which initiated by means of radiation with a jumping along phase,
expediently to operate only at pressures nearby to the left part of breakdown curve. Because at the increasing of
pressure the losses of energy are increased on elastic and non-elastic collisions, that reduces efficiency of discharge.
Authors in first measured a plasma density in low pressure discharge initiated by a microwave radiation with the
jumps of phase with help developing the original technique of the use the double probes of Langmuir, separate
source of direct-current, high-frequency transformers, digital oscilloscope and least-squares method for treatment of
signals, using the special type of function of regression. Показано, что для создания эффективного разряда, инициированного с помощью излучения с прыжками
фазы, целесообразно работать только при давлениях рядом с левой частью кривой пробоя. Потому что при
возрастании давления потери энергии увеличиваются на упругих и неупругих столкновениях, что снижает
эффективность разряда. Авторы впервые измерили плотность плазмы в условиях разряда низкого давления,
инициированного СВЧ-излучением со скачками фазы, при помощи разработки оригинальной методики
использования двойных зондов Ленгмюра, автономного источника постоянного тока, высокочастотных
трансформаторов, цифрового осциллографа и метода наименьших квадратов для обработки сигналов,
используя специальный тип функции регрессии. Показано, що для створення ефективного розряду, ініційованого за допомогою випромінення зі
стрибками фази, доцільно працювати тільки при тисках поряд з лівою ділянкою кривої пробою. Тому що
при зростанні тиску втрати енергії збільшуються на пружних та непружних зіткненнях, що знижує
ефективність розряду. Автори вперше виміряли густину плазми в умовах розряду низького тиску,
ініційованого НВЧ-випроміненням зі стрибками фази, за допомогою розробки оригінальної методики
використання подвійних зондів Ленгмюра, автономного джерела постійного струму, високочастотних
трансформаторів, цифрового осцилографа та метода найменших квадратів для обробки сигналів,
застосовуючи спеціальний тип функції регресії.